Survey Paper On Fusing Medical Images Using Various Transformation Techniques - et. al., Leela.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a days, medical field requires several enhancement in terms of finding more accuracy to identify the optimal result in all aspects especially decision taken from various pictures obtained using new medical devices. Though very advanced technology brought to meet out this issue still more improvement is required in this regard. Wireless telecommunication is a boon for current living people due to its nature of exchanging data across the world. Telemedicine is one of the best application comes under WC. Telemedicine alleviates the problem of rural people and their medication to avoid their transportation from hometown to long distance city similarly medical experts are also highly committed due to time constraints to visit rural people. These issues resolved simply with the support of image fusion method which is collecting several pictures into single picture. Medical expert can be able to decide the problem from fusing images which is attributed under waveatom transform.This paper deals with survey about image fusion and the contribution of waveatom transform along with other images like SPECT,X-ray,MRI,PET,CT etc.